2011
DOI: 10.1063/1.3570827
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman scattering from silver-coated opals

Abstract: We describe surface-enhanced Raman scattering measurements from a benzenethiol monolayer adsorbed on a silver-coated film that is, in turn, deposited on an artificial opal, where the latter is a close-packed three-dimensional dielectric lattice formed from polystyrene spheres. Data for a range of sphere sizes, silver film thicknesses, and laser excitation wavelengths are obtained. Enhancement factors can be in the range of 10(7). To partially explain these large enhancements, we have performed model finite-dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Considering the laser polarization (electric field in the plane of the sample) and the numerous well‐known simulations carried out on hot spots between, e.g. touching wires and film‐on‐nanosphere‐like silvered opal structures, light should be focused into the singularity at the grooves and crevices, thereby corroborating the good accordance between theory and the measurements presented here.…”
Section: Raman Imaging and Spectroscopysupporting
confidence: 85%
See 1 more Smart Citation
“…Considering the laser polarization (electric field in the plane of the sample) and the numerous well‐known simulations carried out on hot spots between, e.g. touching wires and film‐on‐nanosphere‐like silvered opal structures, light should be focused into the singularity at the grooves and crevices, thereby corroborating the good accordance between theory and the measurements presented here.…”
Section: Raman Imaging and Spectroscopysupporting
confidence: 85%
“…The Ag sample with D = 450 nm gave rise to the largest average enhancement of the three types of samples and was estimated to ~120, which unavoidably will be an underestimation because of bleaching. Furthermore, by using a flat metal surface as reference for enhancement estimation, the effect of chemical enhancement (up to ~2 orders of magnitude) is not taken into account, and other approaches for estimating the enhancement with respect to the signal from molecules in a solution also exist . The reported enhancement with respect to the flat reference together with the low cost and simple, reproducible sample fabrication is promising for highly sensitive and versatile Raman‐based detection in sensor applications.…”
Section: Raman Imaging and Spectroscopymentioning
confidence: 99%
“…can affect biomolecules, prevent a target molecule to approach a close proximity of nanoparticles or change characteristic properties of nanoparticles because of their ageing, recrystallization or random formation of aggregates. 35 Nanostructured substrates promise much better reproducibility and less toxicity promoting their SERS applications in biology and medicine, especially in highly sensitive lab-on-a-chip devices [11,12,[26][27][28]. The latter opens up perspectives for rapid monitoring of cells grown directly or captured on such substrates 40 without staining and fixation.…”
Section: Introductionmentioning
confidence: 99%
“…The latter opens up perspectives for rapid monitoring of cells grown directly or captured on such substrates 40 without staining and fixation. Superficial roughness of the substrates can be created by deposition of metal colloids onto surfaces, coupling between continuous metal films and plasmonic particles, vapor deposition of metals, nanocasting and lithography, electrochemical deposition through a template of 45 self-assembled latex spheres, abridging pillar tip spacing by sputtering, self -assembly of large-scale and ultrathin nanoplate films, application of porous substrates [12,[26][27][28]. An important application of SERS in biomedical diagnostics involves studies of hemoglobin (Hb) abnormalities [19,21, 32] caused by erythrocyte malfunction as a result of pathologies of the cardiovascular system or key organs [6,18,19,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…All these findings point towards a broad range of possibilities of introducing spherical dielectric nanoparticles for controlling the optical properties in many applications. In addition, it has been shown that such nanoparticles can be coated with metallic islands for enhanced Raman scattering [15,16]. …”
Section: Introductionmentioning
confidence: 99%